Mechanism for formation of NaBH proposed as low-pressure process for storing hydrogen in borosilicate glass-sodium solid system: a hydrogen storage material - Figen, Aysel Kanturk; Piskin, Sabriye (INDIAN ACAD SCIENCES, 2012)
The mechanism for the formation of sodium borohydride (NaBH was investigated for its ability to store hydrogen in the borosilicate glass-sodium (BSG-Na) solid system under low hydrogen pressure. BSG, which was prepared by melting borax with silica, was used as the starting material in the BSG-Na system that would be prepared to store hydrogen. It was observed that the mechanism for storing hydrogen in the BSG-Na solid system consisted of six steps and when the BSG-Na system was heated under a pressure of 4 atm, which was created through the use of hydrogen atmosphere, the storage of hydrogen occurred at nearly 480A degrees C for approximate duration of 200 min, with the excellent yield (97%). In addition, the hydrogen storage capacity of the NaBH sample was measured using the Au-PS structure, which was designed as a mini-hydrogen cell. It was determined that the minimum amount of NaBH to generate the maximum volume of hydrogen gas was 12 mg/ml at 270 mV.
Keywords: Materials for storage of hydrogen; sodium borohydride; borosilicate glass; mechanism of formation; BOROHYDRIDE; CATALYST; Materials Science